Morpho-histological characterisation of the alimentary canal of an important food fish, Asian seabass (Lates calcarifer) - Kathiresan Purushothaman; Doreen Lau; Jolly M. Saju; Syed Musthaq SK; Declan Patrick Lunny; Shubha Vij; László Orbán (PeerJ, 2016)
Asian seabass (Lates calcarifer) is a food fish of increasing aquaculture importance. In order to improve our understanding on the digestive system and feeding of this species, morphological and histological features of the gut were studied. Morphologically, the Asian seabass gut is defined by a short and muscular esophagus, well-developed stomach and comparatively short intestine. Mucous secreting goblet cells reactive to PAS (Periodic Acid Schiff) and AB (Alcian Blue) stain were present throughout the esophagus. The stomach was sac-like and could be distinguished into the cardiac, fundic and pyloric regions. Gastric glands and mucus cells were predominately present in the cardiac and fundic regions. Five finger-like pyloric caeca were present between the stomach and intestine. The intestine was a short, tubular structure with no morphological differences between the various regions. Histologically, the intestinal regions were similar, the main difference being in the number of goblet cells that increased from anterior to posterior intestine, with 114 ± 9, 153 ± 7 and 317 ± 21 goblet cells in the anterior, mid and posterior regions, respectively. The intestinal epithelium stained positively for PAS, but the staining was stronger for acidic glycoproteins. The rectum was similar to intestine, except for increased goblet cell numbers (anterior rectum: 529 ± 26; posterior rectum: 745 ± 29). Gut morpho-histology did not respond to salinity changes, however, there was a significant reduction of mucosal height, goblet cell numbers and muscularis thickness upon food deprivation.